Occupational and Environmental Safety and Health - Arezes, Pedro M.; Baptista, João S.; Barroso, Mónica P.; Carneiro, Paula; Cordeiro, Patrício; Costa, Nélson; Melo, Rui B.; Miguel, A. Sérgio; Perestrelo, Gonçalo (Studies in Systems, Decision and Control,, 2019)
This book presents a selection of essential issues that have been prioritized in the occupational and environmental area in 2019. It covers both research and best industrial practices in five main fields, i.e. occupational and environmental safety; occupational and environmental hygiene; occupational and environmental health; ergonomics and biomechanics; and psychosocial issues. In addition to this, other works were selected in transversal and emergency areas. Important issues in training, management, robotics, industry 4.0 have also been addressed. The different chapters aimed at covering the perspective of all involved people, such as managers, workers and OSH professionals. This book is intended as a timely reference guide and source of inspiration to OSH researchers, practitioners and organizations operating in a global and international context.